The prevalence of musculoskeletal disorders symptoms and ergonomics risk among engineering, science, and technology students - Fazilah, Abdul Aziz; Nur Amirah, Abdul Hafidz (Springer, Singapore, 2024)
A high prevalence of musculoskeletal disorders (MSDs) has been reported amongst university students related to prolonged demands and multiple study tasks. This study investigated the MSD symptoms and ergonomic risk amongst students who attended online learning classes and prolonged sitting on their study workstations. The study population comprised engineering, science, and technology students (n = 58). The Cornell Musculoskeletal Discomfort Questionnaires (CMDQ) and Rapid Entire Body Assessment (REBA) were used to evaluate body discomfort and posture, respectively. REBA worksheet was employed to assess the entire body posture of the students with 100 and above total body discomfort scores. The body part that obtained higher complaints amongst participating students was the lower back (19.28%) followed by the upper back (17.93%), neck (10.68%), and wrist (right and left) (9.66% and 7.84%). About 13% of participants were exposed to a very high-risk level, and 27% had a high-risk level. The overall mean score was 7.3, under the medium-risk range. MSD symptoms in students are almost highly prevalent. A mean REBA score of 7.3 equals a medium-risk assessment accompanied by guidance to “further investigate, change soon.” The management team in engineering, science, and technology faculties responsible for student health and comfort should prioritize methods to address and control musculoskeletal discomfort.